The underestimated burden of postoperative pulmonary complications in emergency laparotomy: a propensity score-matched analysis - Amati, Anca-Laura; Negruta, Nicoleta; Ebert, Romina; Kümmel, Niklas; Fritzenwanker, Moritz; Wolff, Matthias; Petzoldt, Sebastian; Reichert, Martin; Hecker, Andreas; Justus Liebig University Giessen (My University, 2025)
Introduction: Emergency laparotomy (EL) remains one of the highest-risk procedures in general surgery, characterized by substantial postoperative morbidity and mortality. Despite major advances in perioperative medicine, current enhanced-recovery and infection-prevention protocols are largely derived from elective surgical cohorts and are seldom validated in emergency settings. This lack of EL-specific data represents a critical gap in establishing evidence-based perioperative guidelines for this uniquely vulnerable patient population. Among postoperative complications, pulmonary complications (PPCs) are the most frequent and consequential, affecting 20–40% of patients and significantly impairing recovery and survival. This study aimed to identify preoperative predictors of PPCs and their impact on postoperative mortality, highlighting potentially actionable targets within the constraints of emergency surgical care. Methods: A total of 928 EL patients were analyzed. To control for non-modifiable demographics and comorbidities, propensity score matching generated two cohorts of 328 patients each—those with and without PPCs. Univariate and multivariate logistic regression identified independent preoperative predictors of PPCs, and survival analyses assessed their association with postoperative mortality. Results: Mortality was significantly higher in patients with PPCs (42.1%) than in those without (11.9%). Independent preoperative predictors of PPCs included ASA score (p = 0.0004), hemoglobin level (p = 0.0340), C-reactive protein-to-albumin ratio (CAR) (p = 0.0001), and colonization with multidrug-resistant organisms (MDROs) on preoperative screening (p = 0.0420). Each of these factors also predicted reduced postoperative survival. Notably, 67.3% of MDROs were not covered by initial empiric antibiotic regimens, and 28.6% of Gram-negative MDROs detected preoperatively were later isolated from the airways of patients who developed PPCs. PPC patients colonized with MDROs had a 47% higher 90-day mortality risk compared with non-colonized counterparts (HR 1.46, 95% CI 0.99–2.15). Conclusion: PPCs are the most frequent and deadly complications following EL, and their occurrence substantially worsens survival. Among identified predictors, Gram-negative MDRO colonization represents the most clinically actionable target. Tailoring empiric antibiotic therapy for high-risk, colonized EL patients could represent a pivotal step toward evidence-based, condition-specific perioperative guidelines aimed at reducing pulmonary complication–related mortality.
Keywords: ddc:610